Linearization from Complex Lie Point Transformations - Sajid Ali; M. Safdar; Asghar Qadir (Journal of Applied Mathematics)
Complex Lie point transformations are used to linearize a class of systems of second order ordinary differential equations (ODEs) which have Lie algebras of maximum dimension d, with d≤4. We identify such a class by employing complex structure on the manifold that defines the geometry of differential equations. Furthermore we provide a geometrical construction of the procedure adopted that provides an analogue in R3 of the linearizability criteria in R2.